Short Communication: First report of Thalamoporella rozieri (Bryozoa: Thalamoporellidae) from Andaman waters with reference to its epibiotic colonization on marine sponges - MOHAMMED NAUFAL; K.A. JAYARAJ (Society for Indonesian Biodiversity, 2018)
Naufal M, Jayaraj KA. 2018. Short Communication: First report of Thalamoporella rozieri (Bryozoa: Thalamoporellidae) from Andaman waters with reference to its epibiotic colonization on marine sponges. Biodiversitas 19: 1521-1526. Bryozoans are aquatic, sessile, colonial, fouling invertebrates, which are found in most marine habitats. Considering the ecological and economic consequence due to the biofouling behavior of bryozoans, a far-reaching study has been carried out on it throughout the world. However, Andaman waters are lacking the bryozoan research for last nine decades. A study on the bryozoan distribution in the littoral region in the eastern coasts of the Andaman Islands was carried out during August 2016. This is the first study on the intertidal bryozoans of Andaman Islands and identified a new report of bryozoan Thalamoporella rozieri from Andaman and Nicobar Waters. Tuberosities in the present T. rozieri colonies are large. The minute calcareous spicules are also examined. Our study has also come across an interesting association in which the epibiont bryozoan T. rozieri adhere to the basibiont sponge Placospongia sp on a big rock. The colony of epizoic T. rozieri on the sponge was lengthier and continuous than on other inert host substrata. This may be because of active substrate selection by settling larvae. As both are filter feeders, no deleterious effect was noticed either in the basibiont side of Placospongia or in the epibiont side of T. rozieri.